The Role of Public Business Credit (KUR) at Pegadaian Palu Timur Branch Office in Improving Community Economic Welfare in Palu City (2022–2024) - Kartika Kartika; Santi Yunus; Mohamad Ichwan; Rita Yunus; Vera Sri Endah Cicilia (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2025)
Public Business Credit (KUR) at pawnshops is a financing program aimed at supporting Micro, Small, and Medium Enterprises (MSMEs) in meeting their business capital needs. According to Regulation of the Coordinating Minister for Economic Affairs of the Republic of Indonesia No. 1 of 2023, Public Business Credit (KUR) is a credit or financing facility provided for working capital and/or investment to individuals, business entities, or business groups that have productive and feasible activities but do not yet have additional collateral or whose additional collateral is insufficient. This study aims to determine the role of Public Business Credit (KUR) at Pegadaian Branch Office (CP) Palu Timur in improving community economic welfare in Palu City. This study uses qualitative research methods with a descriptive approach that aims to describe and understand social phenomena based on non-numerical data, such as interviews, observations, or documents, without using statistical tests. The research results show that the KUR program contributes to an increase in business turnover of 20-40% for most customers, improved ability to meet basic household needs, and reduced dependence on informal loans. However, the majority of customers have not been able to expand their business scale by adding workers, so the impact of welfare improvement is still limited to the nuclear family scope. The limitations of this study lie in the limited number of respondents and the research scope that only covers one pawnshop branch, so further research with broader coverage is needed to obtain a more comprehensive picture.